Iron scavenging and myeloid cell polarization - Ludwig, Natalie; Cucinelli, Stefania; Hametner, Simon; Muckenthaler, Martina; Schirmer, Lucas (Trends in immunology, 2024)
Myeloid cells that populate all human organs and blood are a versatile class of innate immune cells. They are crucial for sensing and regulating processes as diverse as tissue homeostasis and inflammation and are frequently characterized by their roles in either regulating or promoting inflammation. Recent studies in cultured cells and mouse models highlight the role of iron in skewing the functional properties of myeloid cells in tissue damage and repair. Here, we review certain emerging concepts on how iron influences and determines myeloid cell polarization in the context of its uptake, storage, and metabolism, including in conditions such as multiple sclerosis (MS), sickle cell disease, and tumors.